Impact of Delayed Chemotherapy Cycles on Remission Rates in Pediatric Sarcoma Patients - Abbas, Sumbal; Karim, Sumera Abdul; Shaheen, Najma; Jameel, Madiha; Anwar, Maha (Biological and Clinical Sciences Research Journal, 2025)
Pediatric sarcomas, particularly Ewing sarcoma and osteosarcoma, are aggressive malignancies that require timely, protocol-based chemotherapy to maximize remission potential. Objective: To evaluate the effect of delayed chemotherapy cycles on remission rates in pediatric patients with Ewing sarcoma and osteosarcoma. Methods: This retrospective observational study was conducted at Shaukat Khanum Memorial Cancer Hospital and Research Center from 2023 to 2024. It included 150 pediatric patients (78 Ewing sarcoma, 72 osteosarcoma). A delayed cycle was defined as any cycle administered more than three days beyond the scheduled protocol date. Data on demographics, tumor type, delay causes, relative dose intensity (RDI), and remission status were collected from medical records. Results: Delays occurred in 92 patients (61.3%), most commonly due to hematologic toxicity (46.7%) and infections (30.4%). Overall remission rates were significantly higher in patients without delays (84.5%) compared to those with delays (58.7%, p = 0.001). In Ewing sarcoma, remission decreased from 79.4% in the no-delay group to 56.8% in the delayed group (p = 0.032), while in osteosarcoma, remission dropped from 91.7% to 60.4% (p = 0.004). Mean RDI was significantly lower in delayed patients (78.6% ± 8.9) versus on-time patients (93.4% ± 5.2, p < 0.001). Conclusion: Delayed chemotherapy cycles are associated with a significant reduction in remission rates in pediatric Ewing sarcoma and osteosarcoma, largely due to reduced dose intensity. Preventing delays through optimized supportive care and addressing logistical barriers should be prioritized to improve treatment outcomes.